(3aGFOI TQjaI JJYdb Hbhdg JYGdi (B" (3Gde JQ Edi GdPjf jRYehf Cfge BefhG HeG CfRd Edjcs - (3eMeO Hf CHj HcQ Hf CjhH Hf bje GdLhRjg, GHf Gdbje, TeS GdOjf, CHh YHO Gddg, J (B751 (3g` s
(3ChdgG (B:s
(3bGd JYGdi (B:" (3Cde JQ Edi GdPjf jRYehf Cfge BefhG HeG CfRd Edjc heG CfRd ef bHdc jQjO Cf jJMGcehG Edi GdWGZhJ s
(3BNQgG (B:s
(3Pdc aEf GdeTGQb acGf GdEbJUGQ Ydi PcQ GdeTGQb ggfG ai ZGjI GdefGSHI ddZQV GdeWdhH aiGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQg aGFOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B56s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs